2017
DOI: 10.1080/14767058.2017.1323329
|View full text |Cite
|
Sign up to set email alerts
|

Maternal/fetal eNOS-Glu298Asp genotypes and their influence on the severity, prognosis, and lipid profile of preeclampsia

Abstract: The eNOS-Glu298Asp variant (in mothers and newborns) in association with dyslipidemia could affect bioavailability of NO and could represent an increased risk for preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In our BNM analyses, we blocklisted potential edges from offspring SNPs to maternal phenotypes and fasting/1-hr maternal metabolites such that no such edge could be included in the estimated models. However, there is evidence that offspring genotype can have limited influence maternal phenotypes [31,32]. Implementing the specified blocklist prevented the discovery of such rare occurrences with our data.…”
Section: Discussionmentioning
confidence: 75%
“…In our BNM analyses, we blocklisted potential edges from offspring SNPs to maternal phenotypes and fasting/1-hr maternal metabolites such that no such edge could be included in the estimated models. However, there is evidence that offspring genotype can have limited influence maternal phenotypes [31,32]. Implementing the specified blocklist prevented the discovery of such rare occurrences with our data.…”
Section: Discussionmentioning
confidence: 75%
“…Any change occurring in this gene can affect the production of NO, which can lead to hypertension, coronary artery disorder, and PE. Furthermore, another study reported the SNP polymorphism in eNOS, also caused endothelial dysfunction, which can increase oxidative stress [ 10 ]. Another study performed on the Turkish population indicated that eNOS gene (Glu298Asp) polymorphism was more prevalent in PE patients and may lead to eclampsia [ 103 ].…”
Section: Genetic Polymorphism and Its Association With Pre-eclampsiamentioning
confidence: 99%
“…[ 9 ]. Furthermore, many maternal, fetal, environmental and genetic risk factors are involved in the development of PE [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, higher lipid concentrations are seen in newborns, which could be associated with a risk of dyslipidamia in adulthood [ 53 ]. In this context, newborns of mothers who have PE, due to dysregulation in the production of or damage to key molecules required for a healthy foetal environment, are at risk of neurological diseases; disabilities such as cerebral palsy, retardation, sensory deficiencies or behaviour disorders; metabolic diseases such as diabetes, hypertension, metabolic syndrome, and dyslipidaemia; and cardiovascular diseases such as coronary heart disease, cerebrovascular disease, and peripheral vascular disease [ 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%